University website accessibility for totally blind users - Hassouna, Mohammed Saleh; Sahari @ Ashaari, Noraidah; Ismail, Amirah (Universiti Utara Malaysia Press, 2017)
Researchers have discovered significant faults in the accessibility of university websites, especially for visually-impaired users.To determine the requirements for totally blind users, this study conducted a comprehensive literature review and accessibility evaluation on 15 Palestinian university websites.The determined factors were used in designing an accessible web page prototype.An online questionnaire was constructed to evaluate the accessibility of the prototype from the blind users’ perspective.From the evaluation of 16 blind participants, it was found that the prototype was highly accessible (mean score 4.19).The regression analysis test was utilised to determine the relationship between the items and the main principles of accessibility. The results show that there are statistically significant differences between these items. In conclusion, the accessibility factors have been indirectly validated.